Pengaruh Faktor-Faktor Keuangan Dan Perilaku Herding Investor Terhadap Underpricing Pada Penawaran Perdana Saham Perusahaan Yang Terdaftar Di Bei - Alviano Renoldy Saputra; Elizabeth Lucky Maretha Sitinjak (JEMAP, 2018)
The purpose of this study is to examine the influence of financial factors (firm liquidity ratio, and non-financial factors (herding behavior) influence on underpricing. There are 73.21 percent of companies experiencing underpricing during the public offering in 2009-2013.Therefore researchers will see the influence financial factors and herding behavior to the underpricing phenomenon.Underpricing is projected as an abnormal return, the liquidity is proxies by the current ratio (CR), the firm's activity is proxies by total assets of turnover ratio (TATO), profitability is projected Return on Assets (ROA), Assets (ROA), leverage is proxies debt to equity ratio (DER). This study uses multiple regression and fulfills all the classical assumptions. The results showed company liquidity, profitability, and herding behavior significantly influence underpricing.